PENYESUAIAN DIRI ANAK JALANAN DI SIMPANG LAMPU MERAH ARIFIN AHMAD PEKANBARU - Leni Rahmawati; Rosmawati Rosmawati; Zulfan Saam (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This research aims to know the description of the characteristics of street childrens and to know the self-adjustment of street childrens in Arifin Ahmad street, Pekanbaru. This research type is descriptive research with a qualitative approach. Data source in this study was the street childrens who were taken as respondents as many as 6 childrens of which 6 childrens have different activity in the day on the street. Data collected using the instruments include observation and structured interviews. The research results obtained by the characteristics of street childrens in the intersection red light Arifin Ahmad, aged 8-18 years, dominated the child-sex male and 1 female child, the majority of street childrens in the region do not attend school, work for 4-6 hours in a day, they still have a close relationship with parents so that communication with parents is still awake, most childrens still have parents, and live together. Street childrens are seen already adjusting to his environment, both physically and socially. The child looks able to adapt with the weather, have a good relationship with friends, neighbors, as well as showing a caring attitude to friends and also to other people who need help, as well as childrens also have been able to find a way in resolving the problem.Key Words: Self-adjustment, The Street Childrens.